Efficacy of SubcutAneous implantable cardioVErter-defibrillators in ≤18 year-old CHILDREN: SAVE-CHILDREN registry. (15th January 2023) - Mori, Hitoshi; Sumitomo, Naokata; Tsutsui, Kenta; Fukunaga, Hideo; Hayashi, Hidemori; Nakajima, Hiroshi; Muraji, Shota; Nabeshima, Taisuke; Kawano, Daisuke; Ikeda, Yoshifumi; Asano, So; Nitta, Junichi; et al.
Abstract: Background: In adult patients, subcutaneous implantable cardioverter defibrillators (S-ICDs) have been reported to be non-inferior to transvenous ICDs with respect to the incidence of device-related complications and inappropriate shocks. Only a few reports have investigated the efficacy of S-ICDs in the pediatric field. This study aimed to investigate the utility and safety of S-ICDs in patients ≤18 years old. Methods: This study was a multicenter, observational, retrospective study on S-ICD implantations. Patients <18 years old who underwent S-ICD implantations were enrolled. The detailed data on the device implantations and eligibility tests, incidence of appropriate- and inappropriate shocks, and follow-up data were assessed. Results: A total of 62 patients were enrolled from 30 centers. The patients ranged in age from 3 to 18 (median 14 years old [IQR 11.0–16.0 years]). During a median follow up of 27 months (13.3–35.8), a total of 16 patients (26.2%) received appropriate shocks and 13 (21.3%) received inappropriate shocks. The common causes of the inappropriate shocks were sinus tachycardia ( n = 4, 30.8%) and T-wave oversensing (n = 4, 30.8%). In spite of the physical growth, the number of suitable sensing vectors did not change during the follow up. No one had any lead fractures or device infections in the chronic phase. Conclusions: Our study suggested that S-ICDs can prevent sudden cardiac death in the pediatric population with a low incidence of lead complications or device infections. The number of suitable sensing vectors did not change during the patients' growth. Highlights: Subcutaneous-implantable cardioverter defibrillators are useful for preventing fatal arrhythmias in patients less than 18 years old. Bending the tunneler was needed for implantations in the younger population. The number of suitable sensing vectors did not change during the follow up. No patients experienced any subcutaneous lead fractures. The common cause of inappropriate shocks was sinus tachycardia and T wave oversensing.